El periodista en el umbral del siglo XXI - Aguinaga, Enrique de (Estudios sobre el Mensaje Periodístico, 2002)
When it is tried to draw the journalist of 21st century immediately is assaulted by the previous question: Of whom we are speaking? It is the rancid question that has not let repeat itself throughout 20th century and that follows without an answer universally admitted: Who is journalist? Or, if it is preferred, of which the professional exercise of journalism consists? The multiple answers, like the multiple evasions, float in the confusion, between the 19th century rhetoric and the implacable mediatic war by the power of our days. In this situation, the author analyses with realism the present figure of the journalist, employee of the industry of the information; but, at the same time, between the ethics and science, he does not lose the hope of which, in this 21st century, finally, the journalist obtains his own identity. Meanwhile, the author offers a practical catalogue of thirty signals to identify journalists